Personalia w Drugim Liście do Tymoteusza 4,9-15 - Wilk, Janusz (Collectanea Theologica, 2017)
The article comprises theological deliberations on the persons referred to by name in 2 Timothy 4:9-15. These persons can be divided into two groups. The first group consists of those who remained with the Apostle Paul, had a positive attitude towards him, or completed missions appointed by Paul during his imprisonment. They are as follows: Crescens (?), Titus, Luke, Mark, Tychicus and Carpus. The second group comprises his closest collaborators who, for unknown reasons, abandoned Paul, or became (or had been from the first meeting) his fierce opponents. Demas and Alexander belong to this group. If we assume that the Second Epistle to Timothy was written by Paul, each of those individuals referred to in the analysed passage occupied, to some extent, the mind of the imprisoned Apostle. If we assume that 2 Timothy is a pseudepigraph, we obtain a list of people who, according to the author of the text, had clear influence on the Apostle of the Nations during his final stage of life. In the times of the early Church, all name-based references to specific people (who were often well regarded] in Christian communities), might have constituted obscure references to current situations in the respective communities of the followers of Jesus Christ.